$\displaystyle c=\lceil\log_{\lceil2^\frac{a}{c}\rceil}2^a\rceil$
$\displaystyle \lceil\log_{\lceil2^\frac{a}{c}\rceil}2^a\rceil$
u should know two things here
$\displaystyle \log a^b = b \log a $
$\displaystyle log_a a = 1 $
$\displaystyle \lceil\log_{\lceil2^\frac{a}{c}\rceil}2^{\frac{ac} {c}}\rceil$
$\displaystyle \lceil\log_{\lceil2^\frac{a}{c}\rceil}\left(2^{\fr ac{a}{c}}\right)^c\rceil=c\lceil\log_{\lceil2^\fra c{a}{c}\rceil}\left(2^{\frac{a}{c}}\right)\rceil=c (1)$
Thanks for your help. I really appreciate it; however, your solution has an error because it assumes $\displaystyle \lceil2^\frac{a}{c}\rceil = 2^\frac{a}{c}$. Since this is not true, then it's wrong to say $\displaystyle \log_{\lceil2^\frac{a}{c}\rceil}2^{\frac{a}{c}} = 1$.